DIFFERENTIAL-PSYCHOLOGICAL CHARACTERISTICS OF COMBATANTS BEFORE AND AFTER RETURNING FROM THE ANTI-TERRORIST OPERATION ZONE - Балабушка, Є. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article presents the results of the analysis of differential-psychological characteristics of the combatants before and after returning from the ATO zone. It is noted that the study of indicators of mental rigidity and the study of its dynamics in the structure of the individual military personnel who have suffered combat stress, enables differentiation in personnel selection, as well as to track the dynamics of posttraumatic stress disorder in rehabilitation work. Key words: differential-psychological characteristics, combatants, anti-terrorist operation.